Draft Annual Plan 2012-2013 (Volume-II) Government of Chhattisgarh - Planning Commission (Planning Commission, 2012)
Proposed Outlays - Major Heads / Minor Heads of Development Proposed Outlay on Continuing and New Schemes Physical Targets and Achievements Statement Regarding Externally Aided Projects Centrally Sponsored Schemes Tribal Sub Plan (TSP) : Financial Outlays Tribal Sub Plan (TSP) : Physical Targets and Achievements Special Component Plan for Scheduled Castes (SCSP - I) - Financial Outlays Special Component Plan for Scheduled Castes (SCSP) II - Physical Targets and Achievements Financial Outlays / Expenditure for Voluntary Sector.
Government of Chhattisgarh, State Planning Commission